2015
DOI: 10.1590/1089-6891v16i34117
|View full text |Cite
|
Sign up to set email alerts
|

FORMAÇÃO E DISTRIBUIÇÃO DO PLEXO BRAQUIAL EM PAPAGAIOS VERDADEIROS (<italic>Amazona aestiva, Linnaeus, 1758</italic>)

Abstract: <title>Resumo</title><p>Procedimentos anestésicos locais são realizados comumente em aves domésticas e silvestres, por ser de baixo custo e de rápida indução, desde que feitos com precisão, o que requer conhecimento anatômico específico da área a ser operada. Este trabalho objetivou estabelecer a origem e a distribuição do plexo braquial do papagaio verdadeiro (<italic>Amazona aestiva</italic>), através da dissecação da pele e da musculatura de 22 papagaios (17 machos e 5 fêmeas),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Same numbers were observed for the chicken (Baumel, 1975), turkey (Moreira et al, 2005) and domestic pigeon (Franceschi et al, 2009). Different findings were reported in blue-fronted parrot (Silva et al, 2015) and vultures (Moreira et al, 2009), where four trunks were formed from the brachial plexus.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Same numbers were observed for the chicken (Baumel, 1975), turkey (Moreira et al, 2005) and domestic pigeon (Franceschi et al, 2009). Different findings were reported in blue-fronted parrot (Silva et al, 2015) and vultures (Moreira et al, 2009), where four trunks were formed from the brachial plexus.…”
Section: Resultsmentioning
confidence: 71%
“…In the blue-andyellow macaws, nerves originating to form brachial plexus from the intervertebral spaces between the tenth cervical vertebra and the second thoracic vertebra (AchoaFilho et al, 2014). In the blue-fronted parrot, brachial plexus was formed by the ventral braches of the C9 to C11 and T1 to T2 spinal nerves (Silva et al, 2015). In the brachial plexus of merlins, a raptor, two trunks were reported as the accessory brachial plexus and the brachial plexus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the nervous origin varies among birds due to the different number of vertebrae in each region, hens presented similarity to the roadside hawks, having the origin of their plexus between the last two cervical segments and the first three thoracic segments (Nickel et al 1977). In the study, it was observed that in the vulture (Coragyps atratus foetens) (Moreira et al 2009), the burrowing owl (Athene cunicularia), the american barn owl (Tyto furcata) (Silva 2016) and blue fronted amazon parrots (Amazona aestiva) (Silva et al 2015) also presented four nervous origins at the cervicothoracic junction, but between different vertebral levels. Differently, Franceschi et al (2009) reported only three nervous origins in pigeons (Columba livia), as well as Nickel et al (1977) in ducks (Anas platyrhynchos) and geese (Anser anser), Moreira et al (2005) in turkeys (Meleagris gallopavo), and Achôa Filho et al (2014) in the blue-andyellow macaw (Ara ararauna).…”
Section: Discussionmentioning
confidence: 99%
“…These trunks cross a triangular hiatus when emerging from the coelomic cavity, cranially occupying this space (Soresini et al 2013). The roadside hawks presented four nervous origins that constituted four short trunks, similar to the blue fronted amazon parrots (Silva et al 2015) and the burrowing owl (Silva 2016). The vulture also presents four nervous origins, but with the formation of three short trunks (Moreira et al 2009).…”
Section: Discussionmentioning
confidence: 99%